Intra-cellular immunosuppressive drugs monitoring: A step forward towards better therapeutic efficacy after organ transplantation?. (September 2016) - Capron, A.; Haufroid, V.; Wallemacq, P.
Graphical abstract: Abstract: Immunosuppressive drugs (IS) used in solid organ transplantation are critical dose drugs with high intra- and inter-subject variability. Therefore, IS therapeutic drug monitoring (TDM), mainly as trough levels analysis, is a major support to patient management, mandatory to optimize clinical outcome. Even though transplant patients undoubtedly benefited by this pre-dose (C0 ) monitoring, the relationship between these C0 concentrations and the incidence of graft rejections remains hardly predictable. Identification and validation of additional biomarkers of efficacy are therefore very much needed. As the main IS effects are mediated through the inhibition of lymphocyte proliferation pathways, direct drug quantification within this target compartment would appear meaningful, providing hopefully more consistent information on drug efficacy. Due to the analytical performances improvement, these intracellular concentrations became accessible for comprehensive studies regarding clinical benefit of intracellular IS TDM after solid organ transplantation. Over the last ten years, number of studies investigated the potential relationship between IS blood and intracellular pharmacokinetics, genetic variability, and clinical efficacy after solid organ transplantation. A recent literature review suggests that calcineurin inhibitors (tacrolimus and cyclosporine) intracellular concentrations appear more closely related to drug efficacy than blood levels. This closer association has however not been described for the m-TOR inhibitors (sirolimus, everolimus) and the antimetabolite (mycophenolic acid). Additional larger and multicenter clinical trials are needed to confirm these observations.